Protective effects of docosahexaenoic acid combined with bilberry extract on myopic Guinea pigs - Lin, Tainan; Hu, Jianzhang; Wen, Qian; Liu, Xiaoting; Lin, Jinghua; Shi, Qiaomei; Lin, Miao; Huang, Weifu (Frontiers in Medicine, 2024)
This study aims to investigate the protective effects of docosahexaenoic acid (DHA) combined with bilberry extract (BE) on myopic guinea pigs. In total, 105 healthy pigmented guinea pigs aged 2 weeks were selected and randomly divided into five groups. The normal control (NC) group received no treatment, while the experimental groups wore −6.0D lenses on the right eye to establish an animal model of lens-induced myopia (LIM). These groups were further divided based on different treatments: normal feeding, DHA treatment, BE treatment, and combined DHA + BE treatment. Refractive error and axial length for both eyes were measured before modeling, after 4 weeks of modeling, and after 8 weeks of treatment. Fundus examination was performed, and choroidal thickness, choroidal vascularity index (CVI), maximal mixed response in dark adaptation (Max-ERG), and cone cell response in light adaptation (Cone-ERG) were measured. After 8 weeks of treatment, we observed a significant reduction in refractive error and shortening of axial length, improvement in fundus condition, and increased choroidal thickness and CVI in the LIM + DHA + BE group. Electroretinogram (ERG) showed that the amplitudes of a-wave and b-wave were enhanced in both Max-ERG and Cone-ERG tests. The LIM + DHA + BE group exhibited superior effects compared to the LIM + DHA group and the LIM + BE group. The combination of DHA and BE delayed the progression of LIM in guinea pigs and was more effective than DHA or BE alone. The synergistic effect of DHA and BE offers a new approach to the prevention and treatment of myopia.